Pengaruh Waktu dan Temperatur terhadap Sifat Mekanik Pasir dan Kualitas Produk Cor dengan Metode Shell Moulding - Roni Kusnowo; Sophiadi Gunara; Syani Ghozali Fauzan (Polinema Press, Politeknik Negeri Malang, 2019)
The shell molding method is one of the processes of coating sand grains in a thermo setting resin which preserves heat on the model. To produce castings products that have good quality and produce maximum mechanical properties from the shell molding process, it must be known that the right procedure stages such as the right heating time. But currently there is no technical procedure that is found that is the right temperature and heating time for making shell molding to produce good surface quality of castings. This study aims to determine the effect of temperatures and heating time on the mechanical properties of RCS (resin coated sand) and the quality of the object castings. A series of testing methods, carried out by heating the RCS on the sample mold bending and hardness test. Testing the mechanical properties of sand includes bending test and hardness test. The time variations used in sand heating are 1 minute, 2 minutes and 3 minutes with temperature variations of 1800C, 2000C, 2200C, 2400C, 2600C and 2800C. After knowing the results of the most optimal temperature and time from testing mechanical properties then making molds using the shell molding method, the molding material used is aluminum. The mold formed from the shell molding method is then cast using NiHard1 material with a temperature of 14000C. The results of the castings will be identified visually and compared with the mechanical properties of the sand obtained. The results of this study obtained the highest value on the graph of the results of mechanical properties testing at a temperature of 2200C with a heating time of 2 minutes. The results of castings best viewed in terms of visual obtained by heating time for 2 minutes and 3 minutes at a temperature of 2200C. This showed that the heating time for 2 minutes and 3 minutes at the temperature of 2200C results in the highest mechanical properties and the best quality of castings for shell molding method.